Perancangan Interior Panti Jompo dengan Fasilitas Terapi Demensia di Surabaya - Lewi, Trifena (Intra, 2016)
Dementia is a disease that is commonly experienced by elderly, especially women. It is also known as Alzheimer or senile disease. Some people take this condition as a natural thing and underestimate it. In fact, dementia is one of the most severe diseases because the sufferer can forget about literally everything, including the way to speak and pronounce words. This design aims to facilitate dementia sufferer with therapy. The main concept of this design is to provide the patients with peace of mind, aiming at making the patients feel more comfortable and providing them with a fighting spirit. The colors and material are warm colors and natural materials, such as woods, natural stones, and bamboo to represent the tropical atmosphere. The design needs to be as simple as possible in order to make the patients feel like they belong there.